Strategi Pengelolaan dan Transformasi Repository Digital di Perpustakaan Universitas Muhammadiyah Surakarta (UMS) - Naoura Naoura; Prawidya Yogi Hapsari; Yusril Akbar Izzul Khaq; Muhammad Idris Sofwan Hadi (Librarium: Library and Information Science Journal, 2026)
This study aimed to analyze the management strategies and digital transformation of the institutional repository at the Library of Universitas Muhammadiyah Surakarta (UMS). The research focused on how repository management is systematically implemented and how the transformation evolved from a manual system to a self-upload digital platform. A qualitative approach was used, employing in-depth interviews, direct observation, and documentation as data collection techniques. The data were analyzed using the interactive model of Miles and Huberman. The findings revealed that UMS Library has undergone a gradual transformation in managing its repository, starting from collecting academic works in CD format to implementing a self-upload system using Eprints. The management strategies included technical infrastructure, institutional policy support, and collaboration with the university’s IT team. Although the repository has positively impacted operational efficiency and academic visibility, it still faces challenges such as storage limitations and the need for ongoing system updates. The study concludes that the success of repository transformation is influenced by the synergy between institutional policy, technology adoption, and human resource involvement.